Sceniczne użycia prozy Iwaszkiewicza. O trzech adaptacjach ’Matki Joanny od Aniołów’ - Dąbrowska, Dorota (Załącznik Kulturoznawczy, 2021)
This article contains a comparative analysis of three contemporary plays that are stagings of the short story Matka Joanna od aniołów by Jarosław Iwaszkiewicz. The aim of the analysis is to examine the relation between the plays and the text of the literary original, to ask questions about the ideological meaning of each of them and to try to determine the meaning of intertextual references and the aesthetic organization of the plays. The title category of ‘use’ of the text refers to the understanding of its interpretation as a process that takes place separately from the intention to remain faithful to the literary original. Using this category makes it possible to analyze the performances, focusing on the question of their degree of faithfulness to the original, and to reflect on the specificity of the autonomous messages they produce.